The Role of Legal Empowerment Based Advocacy for Rural Communities on Structural Social Inequality - Tama, Rifqi Anugrah; Ikrom, Mohamad; Dixon, Edward; Nte, Ngaboawaji Daniel; Idris, Siti Hafsyah (Indonesian Journal of Advocacy and Legal Services, 2023)
Indonesia is a portrait of a legal state, the rights of the people have been protected by the Constitution, contained in the 1945 Constitution of the Republic of Indonesia. Substantially regarding advocacy assistance to the community is regulated in Article 28 of the Constitution of the Republic of Indonesia "Everyone has the right to recognition, guarantee, protection, and legal certainty that is fair and equality before the law". In order to realize what has been mandated by Constitution, the government then issued a Law on Legal Aid, namely Law Number 16 of 2011 which was later referred to as the Law on Legal Aid. This research is specifically to analyze the application provision of legal aid given the role of the advocacy party legal Empowerment Based for Rural Communities Against Structural Social Inequality. This is the extent of the government's attention to upholding justice and eradicating structural social inequalities in rural communities. Viewed from the point of view of the method used, this type of research/approach is a type of normative legal research. The Normative Approach is research that looks at positive legal aspects as well as documents and statutory regulations. Also called doctrinal legal research, namely legal research that uses secondary data.